COMO A TEORIA DE CONCILIAÇÃO DE METAS DESCREVE E EXPLICA UM PEDIDO DE INFORMAÇÃO (Muitas Vozes, 2022)
In this paper, we present how goal-conciliation theory describes and explains a request for information. Rauen’s goal-conciliation theory takes a speaker’s proactive perspective and considers requests for information as antecedent actions toward the hetero-conciliation of higher-level practical goals. In this context, the speaker’s intentional action plan includes the shared mobilization of a hearer she thinks can provide relevant information for this achievement. The description, also mobilizing Sperber and Wilson’s relevance theory, includes the contextualized emergence of the goal; and the contextualized emergence, execution, and checking of the pertinent antefactual abductive hypotheses constituting interactants’ intentional action plans.